Web development with Jade - Lang, Sean (Packt Publishing, 2014)
In Detail Jade is a template engine for node.js and the default rendering engine for the Express web framework. It is a new, simplified language that compiles into HTML and is extremely useful for web developers. Jade is designed primarily for server-side templating in node.js, but it can also be used in a variety of other environments to produce XML-like documents such as HTML and RSS. This practical, example-oriented guide will teach you how to write Jade, utilize its features, and recognize the best ways to organize templates in your projects. With this book, you will avoid the common pitfalls and issues with sparse documentation, allowing you to learn Jade faster and use it more effectively. To understand Jade, we will first examine the reasons for its design and how these translate into a tool that can provide real benefits to you. You will develop confidence with each of the features of the language with the help of practical examples and thorough explanations. We will cover preprocessors, basic syntax, feeding data into templates, and incorporating logic. By the end of this book, you will be able to effectively use essential features such as filters and mixins as well as template inheritance through a block system. To tie it all together, we will also look at some of the best practices to follow when organizing your Jade projects. Use this comprehensive guide to the Jade language to help you become a more efficient web developer. Approach This is a step-by step, tutorial-based book which will enable web developers to explore the functionalities of Jade and learn how to use it to write certain functions and processes for web development. Who this book is for This book is for web developers with at least a basic understanding of HTML and JavaScript. It will enable you to write an easier form of language that then compiles into HTML.